Noninvasive optical temperature sensing behavior of Ho3+ and Ho3+/Er3+ doped tellurite glasses through up and down-converted emissions - Kibrisli, Orhan; Erol, Erdinc; Vahedigharehchopogh, Naji; Yousef, El Sayed; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ELSEVIER SCIENCE SA, 2020)
Optical temperature sensing behavior of Ho3+ and Ho3+/Er3+ doped tellurite glasses are investigated in terms of fluorescence intensity ratio (FIR) method in the range of 298-558 K. Thermal studies reveal that proposed glasses are stable up to approximately 613 K. Optical thermometry investigations are carried out through temperature dependent upand down-converted photoluminescence (PL) emissions. Richness of the up-converted PL spectrum provides versatility, therefore along with the down-conversion spectrum FIRs of four different emission band pairs are calculated and evaluated. Each pair demonstrates varying sensitivity values in the detectable temperature range. Pump power is altered in up-conversion regime from 0.45 to 0.90 W to investigate the rate of change of emission intensities. Reliability of the FIRs is confirmed after several heating-cooling cycles. Judd-Ofelt analysis is also adopted to estimate radiative properties and temperature sensing capabilities of the proposed glasses. The highest possible absolute and relative sensitivities are determined as 0.0172 K-1 and 2.48 %K-1, respectively indicating the potential of Ho3+/Er3+ doped tellurite glasses for their use in noninvasive optical temperature sensing applications. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Temperature sensing; Tellurite glass; Fluorescence intensity ratio; Up-conversion; Down-conversion; UP-CONVERSION LUMINESCENCE; HO3+/YB3+ PHOSPHOR; LASER TRANSITION; ENERGY-TRANSFER; MU-M; SENSITIVITY; DY3+; THERMOMETRY; ABSORPTION; SPECTRA; Engineering; Instruments & Instrumentation